2022
DOI: 10.2196/34872
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Experiences With Digital Technologies in Aging in Place: Qualitative Systematic Review and Meta-synthesis

Abstract: Background Older adults with chronic illnesses or dependency on care who strive to age in place need support and care depending on their illness. Digital technology has enabled the possibility of supporting older adults in their wishes to age in place. However, current studies have mainly focused on the solitary evaluation of individual technologies or on evaluating technologies for specific illnesses. Objective This study aimed to synthesize research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The research reported 19 systematic reviews [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Almost all the reviews dealt with aspects of effectiveness and/or acceptance in some way, and several also dealt with multiple issues at the same time.…”
Section: The Outcome Of the Narrative Review Based On The Umbrella Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…The research reported 19 systematic reviews [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Almost all the reviews dealt with aspects of effectiveness and/or acceptance in some way, and several also dealt with multiple issues at the same time.…”
Section: The Outcome Of the Narrative Review Based On The Umbrella Re...mentioning
confidence: 99%
“…Five systematic reviews [44,45,53,55,60] emphasize the significance of the interplay between electronics, the internet, and assistive technologies (ATs).…”
Section: The Crucial Role Of Internet and Electronics In Enhancing As...mentioning
confidence: 99%
“…Today, technology represents one of the solutions to overcome this process. The concept of “aging in place” has been pointed out in many works [ 3 , 4 ]. As defined by Hechinger et al [ 4 ], “ aging in place is living in one’s own home as long as possible while maintaining social and care networks and autonomy in deciding the type of assistance ”.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of “aging in place” has been pointed out in many works [ 3 , 4 ]. As defined by Hechinger et al [ 4 ], “ aging in place is living in one’s own home as long as possible while maintaining social and care networks and autonomy in deciding the type of assistance ”. However, as is highlighted by this work, the existing literature is fragmented and lacking in effective solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation